Two new species of holothurians of the genus Echinopsolus Gutt, 1990(Echinodermata: Dendrochirotida: Cucumariidae) from the North-Western Pacific - Panina, Elena G.; Stepanov, Vadim G.; Smirnov, Alexei V.; Martynov, Alexandr V. (Zootaxa, 2020)
Two new species of the genus Echinopsolus—E. sanamyanorum and E. onekotanensis are described. This genus is new for North-Western Pacific marine fauna. Echinopsolus sanamyanorum was collected in the Avacha Gulf (south-east coast of Kamchatka), E. onekotanensis—near the Onekotan Island (The Kuril Islands).